Mitigation of PQ issues in EV charging station connected distribution system using novel RSMLI-based shunt APF - Mogilicharla, Veera Narasimha Murthy; Rao, Lingineni Shanmukha; Moparthi, Ranjit Kumar; Chowdary, Tarigopula Jyothika (Institute of Advanced Engineering and Science, 2023)
In the present scenario, the significant use of electric vehicles (EVs) is growing rapidly in the automotive industry due to cheaper transportation, no fossil fuel required, low maintenance, no fuel cost, and low impacts on the environment over the formal internal combustion engine (ICE) vehicles. In actuality, these EVs are powered by batteries that are charged by a utility-grid-based charging facility. A power-electronic conversion-based charging device is used in this charging station to charge the battery packs in the EV system. The problem statement of this work is identified, these conversion devices in charging units proliferate the power quality of the utility grid. To overcome these problems, a classical square-wave inverter-based active power filter (APF) is employed. The major problems in classical inverters are high common-mode voltage, more harmonic profile, high dV/dt stress, high switching stress, and low efficiency. The contribution of this work is proposing the multilevel inverter (MLI) based APF for better compensation over classical inverters. In this approach, a novel reduced-switch MLI-based APF has been proposed for the mitigation of harmonic currents and also enhances the power factor in utility-grid-connected distribution systems. The effectiveness of the proposed reduced-switch multilevel inverter (RSMLI)-APF is validated by integrating the number of charging units with the MATLAB/Simulink tool, and simulation outcomes are shown along with comparisons.